Labor Market Resource Allocation Optimization Based on Principal Component Analysis - Xiaojing Liu (Journal of Mathematics)
As an endogenous mechanism affecting social and economic changes, the allocation of labor affects the overall efficiency and comprehensive level of economic development in a region. Firstly, this paper collects and analyzes the data from 2011 to 2020, then screens out useful data, and predicts the relevant data of the three major industries in 2021 by the grey prediction method and curve fitting method. Secondly, the principal component analysis is used to calculate the weights of indicators such as market share, industrial growth rate, employment contribution rate, and the pulling ability to GDP, and then the strength of each industry is calculated. Finally, the strong industries are determined according to the principle of increasing the intensity of strong industries, so as to provide suggestions for the optimization of the allocation of labor market resources in the three major industries.